2021
DOI: 10.1111/tid.13566
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical outcomes of tuberculosis among kidney transplant recipients in high endemic country

Abstract: Background: Tuberculosis (TB) is considered as a challenge issue in solid organ transplant recipients because of high morbidity and mortality. Active TB after transplant mostly occurs from reactivation of latent infection. Understanding risk factors and clinical information of TB may provide an appropriate prevention and treatment strategies in this specific patient population, however data from high endemic area is scarce.Methods: A matched single-center, case-control study was conducted in our institute. Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Our first analysis comparing TB involvement sites between SOT recipients and non‐SOT individuals showed that the TB cases involving only extrapulmonary organs were similar between the two groups ( p = .174). The SOT recipients had a significantly higher frequency of disseminated TB, including simultaneous involvement of pulmonary and extrapulmonary organs, compared to the non‐SOT population as well as a high rate of pulmonary TB (71%), which was compatible with previous non‐comparative reports; however, our study showed a lower rate of extrapulmonary lesions and cases of disseminated TB 10,13,15,20,36,42,43,47 . In this study, the lymph node was the most common site of extrapulmonary TB.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our first analysis comparing TB involvement sites between SOT recipients and non‐SOT individuals showed that the TB cases involving only extrapulmonary organs were similar between the two groups ( p = .174). The SOT recipients had a significantly higher frequency of disseminated TB, including simultaneous involvement of pulmonary and extrapulmonary organs, compared to the non‐SOT population as well as a high rate of pulmonary TB (71%), which was compatible with previous non‐comparative reports; however, our study showed a lower rate of extrapulmonary lesions and cases of disseminated TB 10,13,15,20,36,42,43,47 . In this study, the lymph node was the most common site of extrapulmonary TB.…”
Section: Discussionsupporting
confidence: 90%
“…Generally, OKT3, T‐lymphocyte depleting antibodies, or a combination of mycophenolate mofetil and tacrolimus (compared to a combination of azathioprine, cyclosporine, and prednisone) may be associated with a higher risk of TB in SOT recipients based on general risk factors for other opportunistic infections 5,9,10 . Two studies have shown that cyclosporine for renal transplants may be related to earlier onset post‐SOT TB compared to recipients using azathioprine and prednisone, but not to a higher frequency of TB 10,36 . Our data showed that the use of ATG or azathioprine was associated with a 1.5‐ or 4‐fold higher adjusted OR, respectively, of SOT recipients developing TB.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The incidence rate of tuberculosis (TB) in kidney transplant (KT) recipients is higher than that in the normal population, and it is associated with unfavorable outcomes including graft loss and mortality 1 . Screening for latent TB (LTBI) in KT candidates can be accomplished by a thorough clinical history and physical examination, chest radiography, and specific tests, including tuberculin skin test (TSTs) and/or interferon gamma release assays (IGRAs).…”
mentioning
confidence: 99%